Training on Anti-Hypertension Gymnastics (SENSASI) in the Community of Cibungur Village, Rancakalong, Sumedang - Reviani, Nia; Suryanegara, Wiradi; A. Simarmata, Vidi Posdo (Asian Journal of Community Services, 2023)
Hypertension is a disease that is nicknamed the silent killer because of its nature, which is sometimes not realized by sufferers but can suddenly result in death. Through Community Service activities (PkM) at the Indonesian Christian University in one of the villages in Rancakalong District, Sumedang, West Java, namely Cibungur Village, where the activities aim to provide education and training in the practice of SENSASI to village residents as an effort to prevent and treat hypertension. From the results of the training which was attended by 27 participants (residents) consisting of 3 men and 24 women with an age range of 30-60 years, the results showed that there was a decrease in the participants' blood pressure (systole and diastole) which was measured before and after the implementation of the practice.